DNA demethylation of CD40L in CD4+ T cells from women with systemic sclerosis: A possible explanation for female susceptibility - Lian, XiaoRi; Xiao, Rong; Hu, Xinhong; Kanekura, Takuro; Jiang, HongYan; Li, YaPing; Wang, YaoYao; Yang, Yan; Zhao, Ming; Lu, QianJin (Arthritis & rheumatology (Hoboken, N.J.), 2012)
Objective Systemic sclerosis (SSc) is an autoimmune disease with a predilection for women. The interaction between CD40 and CD154 (CD40L) is known to be involved in the development of SSc. Although CD40L is overexpressed in patients with SSc, the mechanisms leading to this overexpression are not well understood. We previously demonstrated that DNA demethylation reactivates the silent X chromosome, resulting in CD40L overexpression in healthy women. We hypothesized that CD40L up‐regulation by DNA demethylation and subsequent reactivation of the silent X chromosome in female patients with SSc explain the susceptibility of women to SSc. The aim of this study was to investigate the effect of DNA demethylation on CD40L expression in CD4+ T cells from female patients with SSc. Methods CD40L expression in CD4+ T cells from patients with SSc and healthy control subjects was measured by flow cytometry and real‐time reverse transcription–polymerase chain reaction. Bisulfite sequencing was performed to determine the methylation status of the CD40L regulatory region. Results CD40L expression was significantly elevated in female patients with SSc. The methylation levels of the DNA regulatory sequences were reduced in female patients with SSc compared with healthy women, and there was a significant inverse correlation between the average methylation level and CD40L mRNA expression in female patients with SSc. In contrast, no significant difference was observed in the expression of CD40L between male patients with SSc and male control subjects. The DNA regulatory regions in both male patients and male control subjects were largely unmethylated. Conclusion Demethylation of CD40L regulatory elements on the inactive X chromosome contributes to CD40L overexpression in CD4+ T cells from female patients with SSc.